INHIBISI ENZIM α-GLUKOSIDASE PADA SENYAWA TECTOQUINONE YANG DIISOLASI DARI Syzygium oblanceolatum (C.B.ROB.) MERR - Najib, Ahmad (Makassar Natural Product Journal (MNPJ), 2024)
Syzygium oblanceolatum (C.B.Rob.) Merr. Has several medicinal benefits, empirically its leaf decoction has been used as an antidiabetic. Several representatives of the Syzygium genus have been proposed to possess chemical compounds, nutraceutical values, and biological activities. In particular, previous studies have emphasized the abundance of bioactive chemicals, including flavonoids, phenolic acids, triterpenoids, and volatile compounds. Several representatives of the genus Syzygium have been proposed to possess chemical compounds, nutraceutical values, and biological activities. In particular, previous studies have emphasized the abundance of bioactive chemicals, including flavonoids, phenolic acids, triterpenoids, and volatile compounds. The tectoquinone compound isolated from Syzygium oblanceolatum (C.B. Rob.) Merr based on its chemical structure is a substituted anthraquinone, namely 2-methylanthraquinone. This study aims to determine the Tectoquinone compound as an α-glucosidase inhibitor and determine the IC50 value of the tectoquinone compound. The method of this research was an α-glucosidase inhibition test using ELISA reader instrument by measuring the absorbance at the maximum wavelength of 405 nm using an acarbose comparator. The results of the α-glucosidase inhibition test of the akarbosa comparator had an IC50 value of 0.258 μg/mL and the IC50 value of the tectoquinone compound was 155.184 μg/mL.